Why localization is necessary as a business strategy in emerging markets: The case comparison of Hyundai and Volkswagen - Jungyoun Lee; Jungyeon Kim; Jiwoo Kim; Seungho Choi (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
Localization, the process of establishing the most adequate system in the target market according to the given environment to produce the most viable product in the market, can help multinational enterprises (MNE) to better understand the market, and take the most appropriate actions needed. Business strategies in emerging markets must account for the environment's distinctive characteristics because emerging markets are characterized by underdeveloped institutions, also known as institutional voids. What would be the best strategy to respond to these voids? The primary focus of this article is to investigate how multinational businesses deal with the institutional voids of emerging markets such as the Indian automobile market, and how the different strategies affect the players' performances. By comparing Hyundai Motors Company and Volkswagen Auto Group's different strategical approaches, this research demonstrates that better creation of a local value chain and ecosystem leads to better performance in emerging markets. Survival within emerging markets requires thorough market analysis in an institutional context, and rapid response to environmental shifts resulting from institutional voids. Localization can help in both aspects.
Keywords: 650; localization; institutional void; emerging market; automobile industry; Hyundai; Volkswagen